Pengaruh Hukum Normatif dalam Peningkatan Mutu Pelayanan dan Perlindungan Hukum Tenaga ATLM - Qolbi , Rifqi Syifa’ul (Legalita, 2024)
The purpose of this study is to determine the effect of therapeutic agreements on legal protection efforts of ATLM workers and the effect of improving the quality of health services at LABKESDA Surabaya, The research method used is mixed methods, namely doctrinal normative and empirical law. The results of the study that LABKESDA Surabaya: (1) legal protection of ATLM workers at LABKESDA Surabaya has not been optimal due to the lack of understanding of the treatment of laws and regulations by management in sanctioning ATLM personnel, (2) The quality of health services at LABKESDA Surabaya is good but needs to be developed in the adjustment of the industrial revolution 5.0 which will provide health service efficiency and as a means of tracking when medical disputes occur to protect workers ATLM by the provisions of Article 359,360 of the Civil Code in resolving medical disputes. This study concludes that normative law greatly affects the work culture of ATLM workers which gives birth to ethics, professionalism, and improving the quality of health services, but efforts to protect the law of ATLM workers are still not optimal, which should be the basis for concrete legal practices of ATLM personnel.